2021
DOI: 10.1186/s11671-021-03594-z
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Iron Oxides Based Nanostructures for Applications in Energy Storage

Abstract: The demand for green and efficient energy storage devices in daily life is constantly rising, which is caused by the global environment and energy problems. Lithium-ion batteries (LIBs), an important kind of energy storage devices, are attracting much attention. Graphite is used as LIBs anode, however, its theoretical capacity is low, so it is necessary to develop LIBs anode with higher capacity. Application strategies and research progresses of novel iron oxides and their composites as LIBs anode in recent ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 154 publications
(149 reference statements)
0
17
0
Order By: Relevance
“…[21] This suggests that when using Fe 2 O 3 for battery applications there would be significant advantages to producing it in the form of quasi-2D platelets.Several synthetic routes have been proposed to generate nanoscale α-Fe 2 O 3 of various geometries including 2D platelets. [22][23][24][25] However, current methods are expensive to implement and typically include multiple complex steps which require high temperatures as well as templates or solid supports. A simpler alternative is to use a controllable, soft interfacial method to self-assemble well-defined and mesoporous nanostructures at an immiscible aqueous/organic interface.…”
mentioning
confidence: 99%
“…[21] This suggests that when using Fe 2 O 3 for battery applications there would be significant advantages to producing it in the form of quasi-2D platelets.Several synthetic routes have been proposed to generate nanoscale α-Fe 2 O 3 of various geometries including 2D platelets. [22][23][24][25] However, current methods are expensive to implement and typically include multiple complex steps which require high temperatures as well as templates or solid supports. A simpler alternative is to use a controllable, soft interfacial method to self-assemble well-defined and mesoporous nanostructures at an immiscible aqueous/organic interface.…”
mentioning
confidence: 99%
“…Iron with sulfate solution is reliable and represents stable salt chemistry for all-iron batteries. As saturated potassium sulfate solution is mixed with iron chloride and the pH was adjusted to obtain the anodic electrolyte (iron(II) chloride), which is used as a cathode electrolyte [184] . Although iron(IV) can be easily synthesized, the safety concerns related to the high oxidation state, which prohibit its use.…”
Section: D-block Elements (Transition Metals)mentioning
confidence: 99%
“…Lv et al (2021) reviewed recent advances in the use of novel iron oxides and composites as LIB anodes in addition to electrochemical applications. Iron oxide-based nanostructures films can be synthesized in a variety of ways, including gas-phase deposition, coprecipitation, and electrochemical methods.…”
Section: Applications Of Iron Oxide Thin Filmmentioning
confidence: 99%
“…185 It was found that iron oxide thin film is reported to exhibit high-performance electrodes having excellent cycling life and high rates (i.e., high enough electronic/ionic contact). 186 Lv et al 187 (2021) reviewed recent advances in the use of novel iron oxides and composites as LIB anodes in addition to electrochemical applications. Iron oxide-based nanostructures films can be synthesized in a variety of ways, including gas-phase deposition, coprecipitation, and electrochemical methods.…”
Section: Applications Of Iron Oxide Thin Filmmentioning
confidence: 99%